Cervical neoplasia and human papilloma virus infection in prostitutes. Issue 6 (December 1991) - Gitsch, G; Kainz, C; Reinthaller, A; Kopp, W; Tatra, G; Breitenecker, G
Abstract : OBJECTIVES--To evaluate the prevalence and incidence of PAP smears indicating cervical dysplasia as well as human papillomavirus (HPV) infection in prostitutes. DESIGN--Prevalence and incidence study of cervical dysplasia and HPV infection in prostitutes. For detection and typing of HPV-DNA In Situ Hybridisation (ISH) was performed in tissue samples with CIN gained by colposcopically directed punch biopsies. SETTING--Second Department of Obstetrics and Gynecology, University of Vienna Medical School and STD Clinic of the Public Health Office, Vienna. SUBJECTS--Registered prostitutes attending the STD Clinic of the Public Health Office and a control group. RESULTS--978 prostitutes and 5493 women with unknown cytological anamnesis were compared. Frequency of positive PAP smears was significantly higher in prostitutes (6.13% versus 1.43%). To determine the pick-up rate of cervical dysplasia during one year after negative cytology we compared 722 prostitutes and 3162 controls. Prostitutes showed a significant higher dysplasia pick-up rate (3.05% to 1.07%) compared with controls. HPV detection rate in prostitutes was similar to that in the control group. The distribution of HPV types revealed a higher frequency of "high risk" HPV 16/18 and 31/33 in prostitutes. CONCLUSION--The results demonstrate a higher incidence and prevalence of cervical dysplasia in prostitutes and therefore suggest regular cervical PAP smear screening in registered prostitutes twice a year.